The Relationship Between Reproductive Health Knowledge Level and Awareness of Sexual Harassment in School-Age Children at Sdn Karawaci Baru 6 Tangerang City - Afifah, Jihan; Qolina, Ellya; Milawati, Rina (Rajaki of Tulip Medika Publisher, 2025)
Abstract Background: Sexual abuse of children can have a direct impact on reproductive health, both physically and psychologically. Proper reproductive health education can help children to recognize inappropriate behavior, such as unwanted touching, sexual solicitation, or speech that contains elements of abuse, understand body changes, and improve the ability to protect themselves from sexual abuse. Objective: To determine the relationship between the level of reproductive health knowledge and awareness of sexual harassment based on age, gender, and information sources in school-age children at SDN Karawaci Baru 6 Tangerang City. Methods: The study used a quantitative method with a cross-sectional descriptive design. The sample consisted of 54 students aged 11-12 years at SDN Karawaci Baru 6 Tangerang City selected through total sampling techniques. Analysis of the relationship between independent, dependent and confounding variables using Chi-Square and Mantel-Haenszel tests to determine the existence of relationships and identify confounding variables. Results: The results showed that reproductive health knowledge was in the good category as many as 43 respondents (79.6%) and the level of awareness against sexual harassment in the alert category was 35 respondents (64.8%). Bivariate analysis showed a relationship between reproductive health knowledge level and sexual abuse awareness (p-value = 0.003). The results of the Crude Odds Ratio and the Mantel-Haenszel Odds Ratio showed that the variables of age (p-value=0.011) and source of information (p-value=0.004) had the potential to be confounding variables due to the difference in Odds Ratio >10%, while gender did not show a significant relationship (p-value=0.010). Conclusion: The results suggest that students aged 11–12 years have adequate reproductive health knowledge, which contributes to their heightened awareness of sexual abuse and the importance of self-protection. Keywords: awareness, reproductive health, school-age children., sexual abuse, vigilance.